2011
DOI: 10.1007/978-1-61779-382-0_12
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Mitochondrial Membrane Potential and ROS Formation

Abstract: Mitochondria are considered as the main source of reactive oxygen species (ROS) in the cell. For this reason, they have been recognized as a source of various pathological conditions as well as aging. Chronic increase in the rate of ROS production is responsible for the accumulation of ROS-associated damages in DNA, proteins, and lipids, and may result in progressive cell dysfunctions and, in a consequence, apoptosis, increasing the overall probability of an organism's pathological conditions. The superoxide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
201
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(219 citation statements)
references
References 8 publications
14
201
1
3
Order By: Relevance
“…Astrocytes exposed to DMSO at concentrations of 1.0% also increases Cyt c release and activated caspase 3 expression, and decreases anti-apoptotic protein Bcl-2 expression, supporting the review that rupture of mitochondria is an initial trigger of apoptotic cascades [28], [35]. Furthermore, the present results indicated that DMSO dose-dependently increases mitochondria-derived ROS production, which is consistent with the notion that degenerated mitochondria are the primary site of ROS production [32]. Taken together, these results reveal that mitochondrial impairment is a primary event in the astrocyte toxicity of DMSO.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Astrocytes exposed to DMSO at concentrations of 1.0% also increases Cyt c release and activated caspase 3 expression, and decreases anti-apoptotic protein Bcl-2 expression, supporting the review that rupture of mitochondria is an initial trigger of apoptotic cascades [28], [35]. Furthermore, the present results indicated that DMSO dose-dependently increases mitochondria-derived ROS production, which is consistent with the notion that degenerated mitochondria are the primary site of ROS production [32]. Taken together, these results reveal that mitochondrial impairment is a primary event in the astrocyte toxicity of DMSO.…”
Section: Discussionsupporting
confidence: 91%
“…It has been demonstrated that decreased ΔΨm reduces aerobic metabolism and increases ROS generation [31], [32]. Thus, the generation of mitochondrial ROS in DMSO-treated astrocytes was assessed by detection of MitoSOX-Red, a highly selective detector of superoxide in live cell mitochondria, using the flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that ROS generation was closely related to MMP changes [13, 14]. Thus, we measured the MMP levels in MG-63 and U2OS cells using fluorescent JC-1.…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial actions of nitric oxide (NO), presumably derived from inducible nitric oxide synthase (iNOS), include enhanced cilia motility [83] and airway smooth muscle relaxation, which have been shown to improve symptoms of hyperreactive asthmatic airways in a guinea pig model [82]. However, elevated levels of ROS/RNS, as seen in obstructive airway diseases [85], have been shown to mediate fibroblast activation, mucus hypersecretion, cell injury and production of pro-inflammatory mediators by epithelial cells, and damage macromolecules DNA, lipids and proteins [84,85,86**,87-91]. Oxidative and nitrative stress is associated with loss of superoxide dismutase activity and downstream events characteristic of asthma, including apoptosis, shedding of the airway epithelium, hyperresponsiveness and diminished antioxidant activity [90,92].…”
Section: Mechanisms Of Organic Dust Mediated Oxidative Stress and Antmentioning
confidence: 99%